Determinants of access to hemodialysis services in a metropolitan region of Brazil - Ana Cristina de Oliveira Soares; Monica Cattafesta; Mirian Patrícia Castro Pereira Paixão; Edson Theodoro dos Santos Neto; Luciane Bresciani Salaroli (BMC, 2022)
Abstract Introduction The increasing prevalence of chronic kidney disease has made it a public health issue. Research on access to hemodialysis services is fundamental for appropriate and assertive approaches to the disease. This study analyzed the factors that influence access to hemodialysis services, from the dimensions of availability, accessibility, and acceptability. Methods This was a cross-sectional census epidemiological study involving 1024 individuals in the Metropolitan Region of Brazil in 2019. Data were analyzed using multinomial logistic regression. Results Factors that increase the chance of belonging to the lowest level of access were: age group from 30 to 59 years (OR 2.16, IC95% 1.377-3.383), female (OR 1.74, IC95% 1.11-2.72), and lower income or equal to two minimum wages (OR 1.80, IC95% 1.17-2.76); the factors medium coverage of the family health strategy or the gateway to public health policy in Brazil (OR 0.54, 95%CI 0.29-0.99), no previous conservative treatment (OR 0.59, 95%CI 0.38-0.91), lack of paid work (OR 0.35, 95%CI 0.15-0.85), retirement/sick leave (OR 0.27, 95%CI 0.12-0.64), and self-assessment of health status as bad or very bad (OR 0.62, 95%CI 0.40-0.96) reduced the chance of belonging to the lowest access level. Conclusion Access to hemodialysis services in a metropolis in the southeastern region of Brazil is influenced by contextual, predisposing, enabling, and health needs characteristics. Those who are female, aged between 30 and 59 years, having an income less than or equal to 2 times minimum wage in Brazil, are at the lowest levels of access, which reinforces the role social determinants in health.